2010
DOI: 10.1208/s12249-010-9413-0
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Gelling Gelrite/Alginate Formulations as Vehicles for Ophthalmic Drug Delivery

Abstract: Abstract. The objective of this study was to develop an ion-activated in situ gelling vehicle for ophthalmic delivery of matrine. The rheological properties of polymer solutions, including Gelrite, alginate, and Gelrite/alginate solution, were evaluated. In addition, the effect of formulation characteristics on in vitro release and in vivo precorneal drug kinetic of matrine was investigated. It was found that the optimum concentration of Gelrite solution for the in situ gel-forming delivery systems was 0.3% (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(51 citation statements)
references
References 40 publications
1
49
0
1
Order By: Relevance
“…Balasubramaniam and group developed ion-activated in situ gelling systems for sustained ophthalmic delivery of ciprofloxacin HCl and concluded that the formulated systems provided sustained release of the drug over a period of 8 h in vitro (Sultana et al, 2006). Sultana and co-workers developed an ionactivated, gelrite based in situ ophthalmic gels of pefloxacin mesylate and compared with conventional eye drops and concluded that this system was capable of effective and controlled management of conjunctivitis (Liu et al, 2010). Liu et al in 2010 investigated in situ gelling Gelrite/Alginate formulations as vehicles for ophthalmic delivery and found that the optimum concentration of gelrite solution for in situ gel-forming delivery systems was 0.3% (w/w) and that for alginate solution was 1.4% (w/w; Vodithala et al, 2010).…”
Section: Doxorubicin Poly[(2-ethoxy) Ethoxy Ethyl Vinyl Ether] (Poly(mentioning
confidence: 99%
See 1 more Smart Citation
“…Balasubramaniam and group developed ion-activated in situ gelling systems for sustained ophthalmic delivery of ciprofloxacin HCl and concluded that the formulated systems provided sustained release of the drug over a period of 8 h in vitro (Sultana et al, 2006). Sultana and co-workers developed an ionactivated, gelrite based in situ ophthalmic gels of pefloxacin mesylate and compared with conventional eye drops and concluded that this system was capable of effective and controlled management of conjunctivitis (Liu et al, 2010). Liu et al in 2010 investigated in situ gelling Gelrite/Alginate formulations as vehicles for ophthalmic delivery and found that the optimum concentration of gelrite solution for in situ gel-forming delivery systems was 0.3% (w/w) and that for alginate solution was 1.4% (w/w; Vodithala et al, 2010).…”
Section: Doxorubicin Poly[(2-ethoxy) Ethoxy Ethyl Vinyl Ether] (Poly(mentioning
confidence: 99%
“…Sultana and co-workers developed an ionactivated, gelrite based in situ ophthalmic gels of pefloxacin mesylate and compared with conventional eye drops and concluded that this system was capable of effective and controlled management of conjunctivitis (Liu et al, 2010). Liu et al in 2010 investigated in situ gelling Gelrite/Alginate formulations as vehicles for ophthalmic delivery and found that the optimum concentration of gelrite solution for in situ gel-forming delivery systems was 0.3% (w/w) and that for alginate solution was 1.4% (w/w; Vodithala et al, 2010). The (mixture of 0.2% Gelrite and 0.6% alginate) solution showed a significant enhancement in gel strength at physiological condition.…”
Section: Doxorubicin Poly[(2-ethoxy) Ethoxy Ethyl Vinyl Ether] (Poly(mentioning
confidence: 99%
“…Gellan gum was considered noncarcinogenic based on studies with mice and rats fed with the polysaccharide (0-5 g/kg body weight), wherein no neoplastic or nonneoplastic lesions were observed (Bergfeld et al 2012). Gellan gum (0.2-0.8 %) was also considered as nonirritant to the eyes of rabbits (Liu et al 2010;Ramaiah et al 2007). …”
Section: Toxicity Assessment Of Bacterial Polysaccharidesmentioning
confidence: 99%
“…Such a gelled mixture released in vitro the anticancer drug matrine most slowly. When the solution of this mixture was instilled in rabbit eyes the in situ gelling significantly prolonged drug residence in the precorneal area over the time allowed by the GG or NaAA solution alone (Liu et al, 2010). A further in situ gel-forming polysaccharide mixture is composed of Ch and GG.…”
Section: In Situ-gelling Systemsmentioning
confidence: 99%